Comparative DNA analyses in longstanding ulcerative colitis with aneuploidy. Issue 12 (December 1989) - Löfberg, R; Caspersson, T; Tribukait, B; Ost, A
Abstract : In seven patients with longstanding ulcerative colitis, multiple mucosal biopsies taken at colonoscopy were assessed for DNA content and histological dysplasia. DNA analyses were performed using flow cytometric analyses in biopsies and microspectrophotometry in imprint slides prepared from the biopsies. Abnormal aneuploid DNA content was detected in five of the patients in eight separate locations in the colon. There was good conformity between the two methods in the detection of aneuploidy. Both methods of DNA analysis are considered to be applicable in mucosal biopsies from patients with ulcerative colitis. In two patients with significant low grade dysplasia in association with macroscopical lesions (DALMs), there was a relationship with aneuploid DNA pattern found by flow cytometric or microspectrophotometric analyses. Indefinite changes, probably dysplastic were found in three other patients and two of those also displayed aneuploidy, although only once in the same biopsy location. In five locations aneuploidy was detected without concomitant dysplasia. DNA-aneuploidy seems therefore to appear earlier than dysplasia and may be an early marker of malignant transformation of the mucosa in ulcerative colitis. Prospective trials are needed before the clinical significance of early findings of aneuploidy can be determined.